FRAMEWORK FOR MEASURING URBAN ENERGY SECURITY : CITIZEN PERSPECTIVE - Yudha Prambudia; Arief Rahmana; Anita Juraida (Jurnal Pengembangan Kota, 2019)
The ever increasing urban energy consumption has always been an important issue of urban energy security. Citizen plays critical role in shaping the energy consumption. Therefore, citizen perspective can give significant impact to urban energy security evaluation. This research aims to provide a systematic framework to measure urban energy security taking into account the perspective of citizen and showcase its implementation in a case of Bandung city. The proposed framework is a straight five stages process as follow; (1) establishing the urban context, (2) defining energy security relevant to the context, (3), determining dimensions of energy security , (4) determining indicators and and metrics, and (5) the final stage is calculating energy security. The implementation case shows Bandung’s energy security is at Middle Low status. It also verify that the framework is operationally viable and it can capture the significance of citizen perspective.